1998
DOI: 10.1046/j.1471-4159.1998.70031094.x
|View full text |Cite
|
Sign up to set email alerts
|

High Calcium Permeability of Serotonin 5‐HT3 Receptors on Presynaptic Nerve Terminals from Rat Striatum

Abstract: Abstract:The serotonin 5-HT3 receptor, a ligand-gated ion channel, has previously been shown to be present on a subpopulation of brain nerve terminals, where, on activation, the 5-HT3 receptors induce Ca 2~influx. Whereas postsynaptic 5-HT 3 receptors induce depolarization, being permeant to Naãnd K~, the basis of presynaptic 5-HT3 receptor-induced calcium influx is unknown. Because the small size of isolated brain nerve terminals (synaptosomes) precludes electrophysiological measurements, confocal microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 40 publications
5
71
1
2
Order By: Relevance
“…It is worth noting that the expression of 5-HT3 receptors in the striatum is low in comparison with the PFC and NA. It has been shown that 5-HT3 receptors are present on striatal, potentially dopaminergic, nerve terminals (Nayak et al, 2000) and that striatal presynaptic 5-HT3 receptors are highly permeable to calcium and may facilitate neurotransmitter release by increasing calcium concentrations within the terminal (Ronde and Nichols, 1998). In the PFC, one study has shown colocalization of 5-HT3 receptors with GABAergic cells (Morales et al, 1996).…”
Section: -Ht3 Localizationmentioning
confidence: 99%
“…It is worth noting that the expression of 5-HT3 receptors in the striatum is low in comparison with the PFC and NA. It has been shown that 5-HT3 receptors are present on striatal, potentially dopaminergic, nerve terminals (Nayak et al, 2000) and that striatal presynaptic 5-HT3 receptors are highly permeable to calcium and may facilitate neurotransmitter release by increasing calcium concentrations within the terminal (Ronde and Nichols, 1998). In the PFC, one study has shown colocalization of 5-HT3 receptors with GABAergic cells (Morales et al, 1996).…”
Section: -Ht3 Localizationmentioning
confidence: 99%
“…Among 5-HT receptors, only 5-HT3 is a ligand-gated ion channel, whereas the other receptors belong to the G-proteincoupled receptor (GPCR) superfamily. The striatum expresses a variety of 5-HT receptors: 5-HT1B and 5-HT1E (Bruinvels et al, 1994), 5-HT2A and 5-HT2C (Ward and Dorsa, 1996), 5-HT3 (Blandina et al, 1989;Rondé and Nichols, 1998), 5-HT4 (Jakeman et al, 1994;Waeber et al, 1994;Gerald et al, 1995;Patel et al, 1995), and 5-HT6 (Ruat et al, 1993;Ward and Dorsa, 1996;Gerard et al, 1997). The striatal expression of 5-HT7 is controversial (Vizuete et al, 1997;Martin-Cora and Pazos, 2004).…”
Section: Pharmacological Characterization Of the Receptor Subtypementioning
confidence: 99%
“…3 Postsynaptic 5-HT 3 receptors are present on g-aminobutyric acid (GABA) ergic interneurons, mediating fast synaptic neurotransmission in the CNS, 4,5 while presynaptic 5-HT 3 receptors modulate the release of several neurotransmitters in various brain regions. 2,6-10 Since 5-HT 3 receptors are highly expressed in the caudate nucleus, putamen, hippocampal and amygdala regions, 1,7 it has been suggested that selective 5-HT 3 receptor antagonists may have psychotropic effects.…”
Section: Introductionmentioning
confidence: 99%
“…21 With the exception of clozapine, 22,23 an interaction of neuroleptics with the 5-HT 3 receptor has not been described so far. If neuroleptics are functional antagonists at 5-HT 3 receptors, this might contribute to the pharmacological profile of these antipsychotic agents. Therefore, we studied whether neuroleptics exert antagonistic effects at endogenous neuronal 5-HT 3 receptors and at human 5-HT 3A receptors stably expressed in human embryonic kidney (HEK) cells.…”
Section: Introductionmentioning
confidence: 99%